“You’ve Just Cursed Us”: Precarity, Austerity and Worker’s Participation in the Non-Profit Social Services - Cunningham, Ian; Baines, Donna; Shields, John (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2017)
Though not monolithic, the non-profit social services sector has been an arena where workers and management participated in various forms of shared planning, service development and organizing the labour process. This included: 1- formal participation processes such as collective bargaining with union representation, and 2- practice-profession or task participation. Drawing on 34 qualitative interviews undertaken with a variety of actors (Chief Executive/Senior Directors, senior operational management, Human Resource Managers, frontline staff, and, where available, union representatives) in two non-profit social service agencies in Ontario (Canada), the article traces how these forms of participation have changed as a result of government austerity policies alongside the expansion of precarious employment and funding in the non-profit sector.Using exemplar quotes and qualitative analysis, the article shows that worker’s participation in each form has declined, while management simultaneously has extended greater control over the labour process and removed or reduced forums and opportunities for input from staff. In terms of task participation, measurement and governance structure of New Public Management (NPM) and austerity have led to less autonomy and choice, especially in the area of working time. The study also found that unitarist approaches, intolerant of staff voice and possible dissent, have displaced earlier representative participatory approaches that either utilized the management chain, or embraced and worked constructively with unions. Though these pressures existed prior to the introduction of austerity policies, the data show that decreased worker’s participation coincides and is further undermined by the financial and governance processes associated with NPM and austerity-linked cuts in government and other forms of funding. Overall, the data and analysis suggest that participation in the Non-profit Social Services (NPSS) may be another casualty of this current wave of neoliberalism.